(untitled) (Research, Society and Development, 2021)
As proteins, peptides have a variety of functions, such as structural function, energy reserve, transport, enzymatic, hormonal, and even in the defense of organisms against foreign bodies. As for example the cyclotides, which are a class of peptides that have a closed chain, which end up differentiating themselves from other peptides thanks to the circular conformation different from other peptide structures that are linear, performing an immunological function in plant species. Moreover, this group of peptides has a wide distribution, and currently there are about 50 cyclotides distributed in 5 families of higher plants: Rubiaceae, Solanaceae, Fabaceae, Cucurbitaceae and Violaceae, with the largest distribution is in the family of Violaceae. In the scientific literature there are few studies that portray in depth this group of peptides, therefore this work aims to portray the biosynthesis, main specimens, as well as the main molecular structures of cyclotides.